A new dawn for monoclonal antibodies against antimicrobial resistant bacteria - Troisi, Marco; Marini, Eleonora; Abbiento, Valentina; Stazzoni, Samuele; Andreano, Emanuele; Rappuoli, Rino (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) is a quickly advancing threat for human health worldwide and almost 5 million deaths are already attributable to this phenomenon every year. Since antibiotics are failing to treat AMR-bacteria, new tools are needed, and human monoclonal antibodies (mAbs) can fill this role. In almost 50 years since the introduction of the first technology that led to mAb discovery, enormous leaps forward have been made to identify and develop extremely potent human mAbs. While their usefulness has been extensively proved against viral pathogens, human mAbs have yet to find their space in treating and preventing infections from AMR-bacteria and fully conquer the field of infectious diseases. The novel and most innovative technologies herein reviewed can support this goal and add powerful tools in the arsenal of weapons against AMR.